ダイ12ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1971-1972 - 小口, 高; オグチ, タカシ; OGUTI, Takasi (国立極地研究所, 1974)
P(論文) 1. The 12th wintering party consisting of 29 members was in charge of research activities at Syowa Station for the period from March 1971 to February 1972. Subjects of research were aurora, cosmic rays, geomagnetism, ionosphere, radio physics, meteorology, biology, oceanography, seismology, cartography, glaciology, medical sciences, balloon observation of auroral X-rays and rocket experiments for aurora studies. 2. Seven flights of sounding rockets, one is of S-160 type and 6 are of S-210 type, were carried out for measuring ozone density, electron density, auroral UV and X-rays, magnetic field, electric field and VLF emissions. Close relations were found between auroral visible emissions and X-rays, and between auroral UV and VLF radio emissions. 3. Mizuho Camp (70°42'1S, 44°17'5E) was equipped with a 12 kVA power generator, a living hut, and a boring laboratory. Four members stayed at the Camp for 4 months from October 1971 to January 1972, and performed core-drilling of ice down to the depth of 74 m. 4. A station manual, coded lists of equipments and storages were compiled for the convenience of the succeeding party. departmental bulletin paper